A quiet place. Day one [videorecording (DVD)] - Sarnoski, Michael; Krasinski, John, 1979-; Nyong'o, Lupita; Quinn, Joseph (Actor); Wolff, Alex, 1997-; Hounsou, Djimon, 1964-; Scola, Pat (Paramount, 2024)
"Experience the day the world went quiet... When Samira returns home to New York City, her simple trip turns into a harrowing nightmare when mysterious creatures that hunt by sound attack. Accompanied by her cat Frodo and an unexpected ally, Samira must embark on a perilous journey through the city that has suddnely gone silent, where the only rule is to stay quiet to stay alive" --Container.